Evaluación de la cartera de crédito en la liquidez y rentabilidad de las cooperativas de ahorro y crédito del segmento 3 del cantón Loja, periodo 2019-2021. - Ortega, Patricio Emiliano (2022)
The aim of this study was to evaluate the credit portfolio in terms of liquidity and profitability among the savings and credit cooperatives in segment 3 of the canton of Loja during the period 2019-2021. In order to achieve the objective, a descriptive-analytical approach was used, including a historical analysis for the comparison of results, which subsequently showed that the structure of the gross portfolio is distributed as follows: an average of 91.56% in the maturing loans portfolio and an average of 8.44% in the non-interestbearing and non-performing loan portfolios. The non-interest bearing loan portfolio presents its highest default rate in the microcredit portfolio with an average of 60.67%, and the nonperforming loan portfolio also presents its highest default rate in the microcredit portfolio with an average of 56.97%, increasing the possibilities of affecting the level of credit risk, profitability, and liquidity. The assets are financed mostly with third-party resources averaging 85.23% and with its own resources accounting for 14.77%, its capital structure is considered adequate because it is in line with its normal activity. When compared to December 2020, the revenue at the end of December 2021 posted an annual variation of 24.66%, while the expense account grew by 3.93%. Finally, the net profit, discounting taxes and statutory benefits, showed an increase of 137.21% from 2020 to 2021, compared to a loss of -127.02% from December 2020 to December 2019. Furthermore, through the use of correlations, it was shown that the impact of nonperforming loans on profitability had an inverse effect on profit generation in the financial periods of 2019 and 2020. Similarly, it was shown that the levels of default and coverage of the problematic portfolio are above the general average of the financial system.